Enhanced Antifungal Activity of Electrosprayed Poly (vinyl alcohol)/Chitosan Nanospheres Loaded with Sage Essential Oil on the Viability of Aspergillus niger and Botrytis cinerea - Erarslan, Azime; Karakas, Canan Yagmur; Bozkurt, Fatih; Sagdic, Osman (WILEY-V C H VERLAG GMBH, 2023)
In this study, sage essential oil (SEO) loaded nanoparticles were tested in terms of their antifungal properties. In this respect, the electrospray method was employed to fabricate SEO-loaded nanoparticles (SNPs) by encapsulation of different concentrations (0.0, 0.25 %, 0.5 %, and 1 % v/v) of SEO within poly(vinyl alcohol)/chitosan-based nanoparticles (PVA/Chi NPs). The FTIR, DSC, and SEM analyses divulged that SEO could be successfully encapsulated within nanoparticles, possessing a spherical shape and high thermal stability. The encapsulation efficiency values of SNPs at different concentrations varied between 66.1 and 73.3 %. It was determined that SNPs released 62.56 % of their SEO content within 350 minutes. Moreover, the antifungal activity of SEO against Aspergillus niger and Botrytis cinerea could be increased significantly (p<0.05) after it was encapsulated into PVA/Chi NPs. Based on these findings, suggest that SNPs could be used in food preservation applications as a long-term and natural preservative given their controlled release properties.
Keywords: Antifungal effect; Bioactivity; Delivery system; Electrospraying; Salvia officinalis; L. ESSENTIAL OIL; CHITOSAN NANOPARTICLES; IN-VITRO; CHEMICAL-COMPOSITION; NANOCOMPOSITE NANOFIBERS; ANTIOXIDANT ACTIVITIES; ANTIMICROBIAL ACTIVITY; SUMMER SAVORY; ANTIBACTERIAL; DELIVERY; Chemistry